Effect of Lepidium Sativum Leaves Extract and Pumpkin Seeds on Growth of Pimpinella Anisum - Al-kaisy, Wifak Amjad; Lafta, Aliya H.; Fadhl, Rasha H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The field experiment was conducted at botanical garden of Department of Biology, College of Education for Pure Science/ Ibn-Al-Haitham, University of Baghdad to study the effect of Lepidium sativum leaves extract and pumpkin seeds Cucurbita pepo in two concentrations 10% and 20% on physiological characters ofPimpinella anisum. The results showed that in either concentration plant heights, dry weight, biological yield, economic yield, weight of 100 fruits, harvest index, absolute growth rate (AGR) were all increased and percentage of oil in fruits as compared with control plants